Vascular smooth muscle cell FTO deletion aggravates atherosclerotic plaque instability by promoting VSMC migration through the N6-methyladenosine modification of the COL3A1 mRNA - Zhiliang Yang; Keyong Deng; Jiani Wu; Naqiong Wu; Zhifan Li; Shuang Yang; Mengyi Sun; Dan Liu; Xiaotong Ning; Shufeng Chen; Bin Yang; Jue Ye; et al. (Science China Life Sciences, 2026)

Start-up strategies of a heterotrophic nitrifying-aerobic denitrifying bacterium in moving bed biofilm reactor (MBBR) systems for mariculture wastewater treatment - Tangfeng Liu; Mei Liu; Keyong Jiang; Xudong Zhao; Baojie Wang; Lei Wang (Journal of Environmental Chemical Engineering, 2025)

FACMamba: Frequency-Aware Coupled State Space Modeling for Underwater Image Enhancement - Li Wang; Keyong Shen; Haiyang Sun; Xiaoling Cheng; Jun Zhu; Bixuan Wang (Journal of Marine Science and Engineering, 2025)
Recent advances in underwater image enhancement (UIE) have achieved notable progress using deep learning techniques; however, existing methods often struggle with limited receptive fields, inadequate frequency modeling, and poor structural perception, leading to sub-optimal visual quality and weak generalization in complex underwater environments. To tackle these issues, we propose FACMamba, a Mamba-based framework augmented with frequency-aware mechanisms, enabling efficient modeling of long-range spatial relations for underwater image restoration. Specifically, FACMamba incorporates three key components: a Multi-Directional Vision State-Space Module (MVSM) to model directional spatial context via the proposed 8-direction selective scan block (SS8D), a Frequency-Aware Guidance Module (FAGM) for learning informative frequency representations with low overhead, and a Structure-Aware Fusion Module (SAFM) to preserve fine-grained structural cues through adaptive multi-scale integration. Recognizing the importance of spatial-frequency interaction, our model fuses these representations via lightweight architecture to enhance both texture and color fidelity. Experiments on standard UIE benchmarks demonstrate that FACMamba achieves a favorable balance between enhancement quality and computational efficiency, outperforming many existing UIE methods.

Quercetin attenuates nitrite exposure-induced toxicity in Litopenaeus vannamei via the activation of PI3K/Akt and Epac1/Rap1 signaling pathways - Xuanyi Yang; Mei Liu; Ziwen Ren; Qi Wang; Baojie Wang; Yan Gao; Chen Zhong; Kefeng Xu; Keyong Jiang; Lei Wang (Aquaculture, 2025)

The dynamic features and microbial mechanism of nitrogen transformation in small greenhouse farming system of Pacific white shrimp, Litopenaeus vannamei - Yong Huang; Mei Liu; Keyong Jiang; Chen Zhong; Kefeng Xu; Baojie Wang; Lei Wang (Aquaculture, 2025)

Mechanical properties optimization of edible clove oil/chitosan composite materials by multi-island genetic algorithm for active fresh-keeping packaging applications - Hui Liu; Zhenhua Yin; Cuiyun Liu; Mengxuan Cao; Jianming Sun; Xiaofang Wang; Keyong Tang; Xinchang Pang (Food Packaging and Shelf Life, 2025)

Comparison of biosynthetic astaxanthin with other sources: effects on growth, pigmentation, and environmental stress resistance in Pacific white shrimp, Litopenaeus vannamei - Yingrui Sun; Mei Liu; Keyong Jiang; Chen Zhong; Yan Gao; Baojie Wang; Lei Wang (Aquaculture International, 2025)

Microbial community dynamics and nitrogen transformation associated with turbid-turned culture stage of Pacific white shrimp, Litopenaeus vannamei in small greenhouse farms - Yong Huang; Keyong Jiang; Mei Liu; Baojie Wang; Lei Wang (Aquaculture, 2024)

Pollution investigation of wintertime VOCs in the coastal atmosphere of the Yellow Sea: Insights from on-line photoionization-induced CI-TOFMS - Yingzhe Guo; Ruidong Liu; Mei Li; Jing Li; Xinfeng Wang; Likun Xue; Keyong Hou (Science of The Total Environment, 2024)

Metabolomics and transcriptomics analysis reveals the enhancement of growth, anti-oxidative stress and immunity by (-)-epigallocatechin-3-gallate in Litopenaeus vannamei - Xuanyi Yang; Mei Liu; Keyong Jiang; Baojie Wang; Lei Wang (Fish & Shellfish Immunology, 2024)

A study on the effect of temperature training on compensatory growth and pathogen resistance of post-larval Litopenaeus vannamei - Zhen Zhao; Yuan Liu; Baojie Wang; Keyong Jiang; Kefeng Xu; Chen Zhong; Yan Gao; Mei Liu; Lei Wang (Aquaculture International, 2024)

Comparative analysis of transcriptomics and metabolomics provides insights into the mechanisms of VPAHPND invasion and hepatopancreatic damage in Litopenaeus vannamei - Zhen Zhao; Baojie Wang; Keyong Jiang; Mei Liu; Lei Wang (Fish & Shellfish Immunology, 2024)

Uncovering chromatin accessibility and cancer diagnostic potential via cell-free DNA utilization - Jie Li; Jiahui Chen; Xin Sun; Heli Yang; Keyong Sun; Chang Liu; Yongwang Wang; Mengyue Xu; Xin Ji; Ji Zhang; Xiaojiang Wu; Anqiang Wang; et al. (Science Bulletin, 2024)

Fabrication and characterization of fish gelatin/soluble soybean polysaccharide edible blend films through complex coacervation - Yiwei Wang; Jie Liu; Yidan Ding; Xuejing Zheng; Yongchao Jiang; Keyong Tang (Food Hydrocolloids, 2024)

Contrasting fluids and implications for ore genesis in the Jiawula-Chaganbulagen Porphyry Mo-epithermal Pb Zn metallogenetic system: Evidence from fluid inclusions and H-O-He-Ar isotopes - LiXue Sun; Wenyuan Wang; Gang Li; Keyong Wang; Wenju Li; Feng Tian; Zhigao Wang (Geochemistry, 2024)

The potential mechanisms for isoliquiritigenin on the growth and immune regulation of Penaeus vannamei revealed by transcriptomic and metabolomic - Xuanyi Yang; Mei Liu; Qinlang Liang; Keyong Jiang; Baojie Wang; Lei Wang (Aquaculture, 2024)

Metabolomics signature of blood pressure salt sensitivity and its link to cardiovascular disease: A dietary salt-intervention trial - Zhennan Lin; Jianxin Li; Fangchao Liu; Jie Cao; Shufeng Chen; Jichun Chen; Keyong Huang; Yaqin Wang; Hongfan Li; Yan Wang; Jianfeng Huang; Dongfeng Gu; et al. (Science China Life Sciences, 2024)

The combined analysis of transcriptomics and metabolomics reveals the mechanisms by which dietary quercetin regulates growth and immunity in Penaeus vannamei - Xuanyi Yang; Baojie Wang; Keyong Jiang; Kefeng Xu; Chen Zhong; Mei Liu; Lei Wang (Fish & Shellfish Immunology, 2024)

MnOx Nanoparticle-loaded polyacrylonitrile fibers for efficient catalytic ozonation of toluene - Wenjie Duan; Keyong Tang; Liang Zhao; Zhenbang Tian; Jing Wang; Yadi Hu; Jinbao Huang; Xinxin Xu (Atmospheric Pollution Research, 2024)

Effects of dietary Saccharina japonica and Pyropia yezoensis enzymatic hydrolysate on growth, nonspecific immunity, and resistance to Vibrio harveyi in hybrid grouper (Epinephelus fuscoguttatus♀ × Epinephelus lanceolatu♂) - Jing Liu; Sudong Xia; Keyong Jiang; Lihua Geng; Yang Yue; Ning Wu; Quanbin Zhang; Jing Wang (Aquaculture International, 2024)

Insights into the fatty acid binding protein of Pacific white shrimp (Litopenaeus vannamei) suffering acute hepatopancreatic necrosis disease infection - Xiaoqian Gu; Baojie Wang; Keyong Jiang; Mei Liu; Lei Wang (Aquaculture, 2023)

Effects of salinity training on growth performance, osmotic regulation, and pathogen resistance of post-larval Litopenaeus vannamei - Yuan Liu; Baojie Wang; Keyong Jiang; Zhiqun Zhao; Mei Liu; Lei Wang (Aquaculture, 2023)

Fruit and vegetable consumption, cardiovascular disease, and all-cause mortality in China - Jun Wang; Fangchao Liu; Jianxin Li; Keyong Huang; Xueli Yang; Jichun Chen; Xiaoqing Liu; Jie Cao; Shufeng Chen; Chong Shen; Ling Yu; Fanghong Lu; et al. (Science China Life Sciences, 2022)

Fluid evolution and ore genesis of the Lianhuashan lode gold deposit, northern North China Craton: evidence from fluid inclusions and H–O–C–S–Pb isotopes - Kaituo Shi; Keyong Wang; Rui Wang (Arabian Journal of Geosciences, 2021)

Sources of the Laoxiongdong carbonate-hosted Pb–Zn deposit in Southwest China: constraints from S–Pb–Zn isotopic compositions - Wenyuan Wang; Jianguo Gao; Keyong Wang; Yangxia Nong (Acta Geochimica, 2020)

Fluid inclusion and H–O isotope study of the Jiguanshan porphyry Mo deposit, Xilamulun Metallogenic Belt: implications for characteristics and evolution of ore-forming fluids - Changhong Wang; Keyong Wang; Wenyan Cai; Jian Li; Hanlun Liu; Yicun Wang (Acta Geochimica, 2020)

Factors Controlling Deposition of Metallic Minerals in the Meng’entaolegai Ag-Pb-Zn Deposit, Inner Mongolia, China: Evidence from Fluid Inclusions, Isotope Systematics, and Thermodynamic Model - He Yang; Wanli Ma; Rui Wang; Xueli Ma; Keyong Wang (Journal of Earth Science, 2020)

A comparative transcriptomic analysis in late embryogenesis of the red claw crayfish Cherax quadricarinatus - Yan Wang; Baojie Wang; Xuqing Shao; Mei Liu; Keyong Jiang; Mengqiang Wang; Lei Wang (Molecular Genetics and Genomics, 2020)

Geology, fluid inclusion, and stable isotope study of the skarn-related Pb–Zn (Cu–Fe–Sn) polymetallic deposits in the southern Great Xing’an Range, China: implications for deposit type and metallogenesis - Chengyang Wang; Jianfeng Li; Keyong Wang; Qi Yu; Guanghu Liu (Arabian Journal of Geosciences, 2018)

Age, genesis, and tectonic setting of the Mo-W mineralized Dongshanwan granite porphyry from the Xilamulun metallogenic belt, NE China - Xuebing Zhang; Keyong Wang; Chengyang Wang; Wen Li; Qi Yu; Yicun Wang; Jianfeng Li; Duo Wan; Guanghuan Huang (Journal of Earth Science, 2017)

Molecular Cloning of Hemocyanin cDNA from Fenneropenaeus chinensis and Antimicrobial Analysis of Two C-terminal Fragments - Chuwen Qiu; Jie Sun; Mei Liu; Baojie Wang; Keyong Jiang; Shujuan Sun; Xiaolin Meng; Zuoyong Luo; Lei Wang (Marine Biotechnology, 2014)

Purification and identification of a clotting protein from the hemolymph of Chinese shrimp (Fenneropenaeus chinensis) - Baojie Wang; Hongni Peng; Mei Liu; Keyong Jiang; Guofan Zhang; Lei Wang (Journal of Ocean University of China, 2013)